Theorising painkiller (mis)use in football using Bourdieu's practice theory and physical capital - Read, D.; Smith, A. C. T.; Skinner, J. (International Review for the Sociology of Sport, 2023)
This conceptual article advances the value of Bourdieu's practice theory and physical capital as a tool to understand the various types of painkiller (mis)use in sport. Consuming painkillers to manage injury and fatigue is a common practice among male professional footballers and misuse can exacerbate existing injuries and contribute to chronic physical and mental health conditions. In order to highlight the interaction between micro and macro-level factors we conceptualise painkiller use in professional football as a relational process between habitus, capital, and field position wherein variation in use is a result of social trajectory and field experiences. The analysis elaborates upon Bourdieu's practice theory in sport. It shows that the importance of protecting physical capital stems from internalised dispositions about how the body is viewed, which legitimise the use of painkillers within the social field of football despite the damaging potential outcomes for players. The article extends Bourdieu's practice theory to managing painkiller (mis)use, provides recommendations towards a future research programme, and identifies potential interventions for improving athlete welfare.